Frequency and prognostic impact of periprocedural myocardial infarction determined by various MI definitions in patients with chronic coronary syndromes undergoing percutaneous coronary intervention. (14th October 2021) - Ueki, Y; Otsuka, T; Bar, S; Koskinas, K; Losdat, S; Heg, D; Zanchin, T; Siontis, G; Praz, F; Haner, J; Susuri, N; Stortecky, S; et al.
Abstract: Background: Several definitions of peri-procedural myocardial infarction (MI) requiring different biomarker thresholds with or without ancillary criteria for myocardial ischemia are currently recommended without being fully validated in real-world patients with chronic coronary syndrome (CCS) undergoing percutaneous coronary intervention (PCI). Objectives: We aimed to evaluate the prevalence and prognostic value of high-sensitivity cardiac troponin-based peri-procedural MI according to contemporary MI definitions using a large real-world PCI cohort. Methods: In CCS patients undergoing elective PCI enrolled to the Bern PCI registry (NCT02241291) between 2010 and 2018, peri-procedural myocardial injury and infarction were assessed according to the 4th and 3rd universal definition of MI (UDMI), academic research consortium (ARC)-2, and Society for Cardiovascular Angiography and Interventions (SCAI) criteria. The primary endpoint was cardiac death at 1 year. Results: Among 4404 CCS patients, peri-procedural MI defined by the 4th UDMI, 3rd UDMI, ARC-2, and SCAI were observed in 14.9%, 18.0%, 2.0%, and 2.0% of patients, respectively. Cardiac mortality at 1 year in patients with peri-procedural MI defined by 4th UDMI, 3rd UDMI, ARC-2, and SCAI were 3.0%, 2.9%, 5.8%, and 10.0%, respectively. After multivariate adjustments, peri-procedural MI defined by the ARC-2 and SCAI were independently associated with cardiac death at 1 year, while those defined by the 4th and 3rd UDMI were not. Conclusion: Among CCS patients undergoing PCI, periprocedural MIs defined by theARC-2 and SCAI occurred 7 to 9 times less frequently as compared with the 4th and 3rd UDMI, and were the only definitions significantly associated with cardiac mortality. FUNDunding Acknowledgement: Type of funding sources: None.